PERSONAL DATA PROTECTION IN INDONESIA'S DIGITAL LAW ENFORCEMENT SYSTEM - Hadi Purnomo (GoAcademica Research dan Publishing, 2026)
The rapid digitalization of law enforcement in Indonesia has increased the use of personal data in investigative, intelligence, and criminal justice processes. While digital technologies improve the effectiveness and efficiency of law enforcement, they also create significant risks to privacy rights and personal data protection. The enactment of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) represents an important milestone in establishing a comprehensive legal framework for personal data protection. However, challenges remain in ensuring the effective implementation of personal data protection principles within digital law enforcement practices. This study aims to analyse the implementation of personal data protection in Indonesia’s digital law enforcement system, identify the challenges encountered, and formulate strategies to strengthen legal protection mechanisms while maintaining a balance between law enforcement interests and the protection of individual privacy rights. This research employs normative legal research using statutory, conceptual, and comparative approaches. Legal materials were collected through library research consisting of primary, secondary, and tertiary legal sources and analysed qualitatively through inventorying, classifying, interpreting, and systematically examining relevant legal norms and doctrines. The findings indicate that the implementation of personal data protection remains constrained by the absence of specific technical regulations, limited institutional capacity, weak supervisory mechanisms, and the growing use of artificial intelligence, facial recognition, big data analytics, and digital surveillance technologies. The study also reveals a gap between regulatory norms and practical implementation that may undermine privacy rights and legal certainty. The novelty of this research lies in proposing an integrated strengthening model based on regulatory harmonization, independent oversight, institutional capacity building, and privacy-by-design principles to support accountable, transparent, and human rights-oriented digital law enforcement.